2004
DOI: 10.1111/j.0030-1299.2004.12934.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphipod crustacean size spectra: new insights in the relationship between size and oxygen

Abstract: Chapelle, G. and Peck, L. S. 2004. Amphipod crustacean size spectra: new insights in the relationship between size and oxygen. Á/ Oikos 106: 167 Á/175.Oxygen availability limits the maximum potential size attainable in benthic gammaridean amphipods from the suborder to the generic level, while also influencing size within species. In this paper we investigate the effect of oxygen on 15 size spectra worldwide, established by compiling maximum length data of more than 2000 amphipod species. We used TS95/5 as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 55 publications
(76 reference statements)
2
50
0
Order By: Relevance
“…Assuming a proportional increase in intake under high oxygen causes an increase in both optimum and maximum size. Such a pattern is consistent with the observations of Chapelle and Peck (2004) for amphipods. Varying cost as a function of oxygen concentration rather than intake yields qualitatively similar results, a Energy intake and energy cost as a function of body mass, b Energy surplus as a function of mass experimental timescales.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Assuming a proportional increase in intake under high oxygen causes an increase in both optimum and maximum size. Such a pattern is consistent with the observations of Chapelle and Peck (2004) for amphipods. Varying cost as a function of oxygen concentration rather than intake yields qualitatively similar results, a Energy intake and energy cost as a function of body mass, b Energy surplus as a function of mass experimental timescales.…”
Section: Discussionsupporting
confidence: 92%
“…The consistency of the relationship between maximum size and oxygen concentrations across both marine and fresh water environments and across elevation strongly supports the hypothesis that oxygen limits maximum size in amphipods. Chapelle and Peck (2004) further found that oxygen availability is not only associated with maximum size; in fact, it is positively associated with every size quantile, with the slope of the relationship becoming steeper for the higher size quantiles. The linear relationship between oxygen concentration and body length suggests that respiration in these amphipods is aided by circulation and/or allometric scaling of gill size, rather than occurring simply via diffusion.…”
Section: Experiments On Oxygen and Sizementioning
confidence: 85%
“…At a certain size, the circulatory system cannot cope with the demand for oxygen during activity, creating a ceiling for metabolic performance (Chapelle and Peck 1999, Peck et al 2009, Glazier 2010, Pö rtner 2010, Verberk et al 2011). This concept was used to understand evolutionary patterns of size among terrestrial insects (Harrison et al 2010) or ecological patterns of size among marine amphipods (Chapelle and Peck 2004). Following this theory, hypoxia should lower the ceiling on maximal possible body size such that rotifers become smaller regardless of their temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In Hong Kong, M. longidactyla is generally found in algal tufts where the water current is strong and, in agreement with our results, they should be sensitive to low oxygen levels. Chapelle & Peck (2004) hypothesized that oxygen availability limits the maximum potential size attainable in benthic gammaridean amphipods on an evolutionary time scale. Using quantile regression, McClain & Rex (2001) found that the maximum size in deep-sea turrid gastropods increases with increasing oxygen levels.…”
Section: Discussionmentioning
confidence: 99%